REVIEW OF EMERGING OPTICAL AND WIRELESS ACCESS TECHNOLOGIES - Jagjeet Singh, Jatinder Singh Bal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The bandwidth interest of telecommunication network is becoming quickly because of the rising number of technology-keen end-users. The arising optical and wireless access networks are consistently contending with one another to give these necessities to the end-users. The optical access networks give gigantic data rate and significant distance connect, yet it is less ubiquitous. The wireless access networks furnish adaptable and ubiquitous communication with a low sending cost. In any case, its organization adaptability is limited by the spectrum and reach impediments. The hybrid wireless optical broadband access network (WOBAN) is a strong mix of optical backhaul and wireless front-end to add to a decent versatility, financially savvy and adaptable communication system. This paper reviews the emerging optical and wireless access technologies.